2011
DOI: 10.1177/1099800410395569
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Sleep in Young Patients With Diabetes and Their Families

Abstract: Objective We examined sleep in families of individuals with type 1 diabetes and the relationship of sleep with obesity, diabetes, and insulin resistance. Methods Probands with type 1 diabetes diagnosed before age 18 and 1st and 2nd degree relatives were included (n = 323). Demographic, anthropometric and clinical variables and self-reported sleep duration and napping were assessed. Results On average, adults (≥ 20 years) slept 7.5 (SD 1.5) hr, whereas children (5–11 years) and adolescents (12–19 years) sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 30 publications
0
36
0
1
Order By: Relevance
“…After employing inclusion and exclusion criteria to the full manuscripts, 13 studies were excluded because of lack of findings related to overweight or obesity and/or physical activity or lifestyle, and one was excluded because the study focused on eating disorders. In total, seven manuscripts met inclusion criteria for our review, including the one publication from a nursing journal (Estrada, Danielson, Drum, & Lipton, 2012). No additional manuscripts were identified from reviewing the reference lists of the articles included in this review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After employing inclusion and exclusion criteria to the full manuscripts, 13 studies were excluded because of lack of findings related to overweight or obesity and/or physical activity or lifestyle, and one was excluded because the study focused on eating disorders. In total, seven manuscripts met inclusion criteria for our review, including the one publication from a nursing journal (Estrada, Danielson, Drum, & Lipton, 2012). No additional manuscripts were identified from reviewing the reference lists of the articles included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…The age range varied from 4 to 18 years, but for those studies that reported the mean age, most focused on the preadolescent to adolescent years of 11–16 years. In only one study was a diverse sample in terms of race/ethnicity reported (Estrada et al, 2012). Diabetes duration ranged from an average of 3.7 to 7.4 years, and mean HbA1c levels ranged from to 7.5% to 13.1%, whereas the American Diabetes Association recommends levels <8.0% in this age group (Silverstein et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…385,386 In the general adult population and in healthy children and adolescents, sleep alterations may adversely influence glucose regulation, 385 C-reactive protein, 387 and lipids 388 and increase the risk for hypertension, T2DM, heart attack, and stroke. 389,390 Reports of reduced sleep times of up to 64% 391 have been documented for children and adolescents with diabetes mellitus who confront additional challenges with sleep as a result of diabetes mellitus management 392,393 that may further disrupt sleep and add to adverse cardiovascular outcomes.…”
Section: Sleepmentioning
confidence: 99%
“…Insufficient sleep is associated with cancer, weight gain, anxiety, depression, suicide, cardiovascular disease, 25 and immune dysfunction, and thus is an important health issue in the population at large. [26][27][28][29][30][31][32] As individual's sleep need is unique, screening for insufficient sleep requires direct questioning about sleep need in comparison to total sleep achieved and/or inquiring about the presence of the consequences of inadequate sleep as opposed to just asking how much sleep the person obtains. BRFSS#1 attempts to screening for non-restorative sleep or perhaps just not feeling rested, but is not specific for detecting either sleep disorders or lack of sleep opportunity.…”
Section: Screening For Non-restorative or Insufficient Sleepmentioning
confidence: 99%